Anti-Mullerian hormone concentrations are inversely associated with subclinical atherosclerosis in premenopausal women. (25th November 2020) - Delialis, D; Lamprinoudaki, I; Stergiotis, S; Patras, R; Chatzivasileiou, P; Augoulea, A; Anagnostis, P; Armeni, E; Rizos, D; Kaparos, G; Alexandrou, A; Georgiopoulos, G; et al.
Abstract: Background: Anti-Müllerian hormone (AMH) constitutes a marker of ovarian reserve and appears to have a predictive role regarding the time of menopause. Moreover, AMH is associated with adverse cardiac events. History of premature menopause and early onset of menopause have been associated with increased risk of cardiovascular (CV) disease. In addition, menopausal transition and duration of menopause have been associated with increased burden of subclinical atherosclerosis. However, the association between AMH as a marker of female reproductive age with atherosclerosis in premenopausal women is currently unknown. Purpose: To investigate whether AMH concentrations are associated with markers of early atherosclerosis in healthy, normally menstruating women. Methods: In a cross-sectional study, vascular structure and function were assessed by measurement of carotid and femoral intima-media thickness (IMT), lipid profile and serum AMH concentrations were assessed. Exclusion criteria were clinically overt CV disease, abnormal ovulatory cycles, polycystic ovarian syndrome, acute infection or chronic inflammatory disease, risk factors for CV disease and any medication Results: Seventy premenopausal women, aged 32.7±6.5 years, were included. Mean AMH levels were lower in smokers than in non-smokers and negatively associated with total cholesterol (TC) levels. An inverse association between mean AMH concentrations and IMT in all segments was observed. No correlation with other markers of subclinical atherosclerosis or traditional CV risk factors was found. After multi-variable adjustment for traditional CV risk factors, the association between AMH concentrations combined IMT and carotid bulb IMT, remained significant. Conclusions: In healthy, normally ovulating women, low AMH concentrations are associated with an adverse lipid profile and subclinical atherosclerosis, independently of traditional CV risk factors. This finding suggest a role of decreased follicular reserve with atherosclerotic disease. Funding Acknowledgement: Type of funding source: None